2016
DOI: 10.4049/jimmunol.1402709
|View full text |Cite
|
Sign up to set email alerts
|

S100A8 Production in CXCR2-Expressing CD11b+Gr-1high Cells Aggravates Hepatitis in Mice Fed a High-Fat and High-Cholesterol Diet

Abstract: Nonalcoholic fatty liver disease (NAFLD) is a common chronic liver disease with a spectrum of presentations. S100A8 has been suggested to play a pivotal role as an endogenous immune-activator in inflammatory diseases. In this study, we investigated the involvement of S100A8 in the development of NAFLD. We used a diet model of NAFLD, in which mice were fed either a high-fat and high-cholesterol diet (HFHCD) or a normal diet (ND) as a control. We also assessed liver tissues from patients with NAFLD, including pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“… 6 A total of 25 calcium-binding S100 family members, namely S100A1–18, hair hyaluronin, keratin fibrin, repetin, S100B, S100P, S100Z, and S100G, have been currently identified. 7 As indicated by Mukai, et al, 8 S100A8 could induce the upregulation of tumor necrosis factor-alpha (TNF-α) in CXCR2-expressing CD11b + Gr-1 high cells, thereby aggravating hepatitis in mice. In addition, Liu, et al 9 also found that expression levels of S100A9 was significantly elevated in patients with non-alcoholic fatty liver, which were suggested to be even higher in patients with NASH, highlighting the involvement of S100 protein in NAFLD progression.…”
Section: Introductionmentioning
confidence: 96%
“… 6 A total of 25 calcium-binding S100 family members, namely S100A1–18, hair hyaluronin, keratin fibrin, repetin, S100B, S100P, S100Z, and S100G, have been currently identified. 7 As indicated by Mukai, et al, 8 S100A8 could induce the upregulation of tumor necrosis factor-alpha (TNF-α) in CXCR2-expressing CD11b + Gr-1 high cells, thereby aggravating hepatitis in mice. In addition, Liu, et al 9 also found that expression levels of S100A9 was significantly elevated in patients with non-alcoholic fatty liver, which were suggested to be even higher in patients with NASH, highlighting the involvement of S100 protein in NAFLD progression.…”
Section: Introductionmentioning
confidence: 96%
“…Although a methionine-choline-deficient diet has been shown to induce steatohepatitis, which is morphologically similar to NASH, it does not lead to body weight gain and obesity [16]. On the other hand, mice on high-fat diets have been used as NAFLD models [17, 18], and little is known about CnP-mediated attenuation of NAFLD in high-fat diet mouse model.…”
Section: Introductionmentioning
confidence: 99%
“…For example, TRAIL −/− mice are protected from inflammation when subjected to a high fat–high fructose diet through the attenuation of both hepatocellular death and macrophage activation . Tumor necrosis factor α is also produced through the calcium and zinc binding protein S100A8 as an endogenous ligand for Toll‐like receptor‐4 in bone marrow‐derived macrophages, thereby contributing to NASH‐associated inflammation …”
Section: What Are the Players During Hepatocyte Lipoapoptosis?mentioning
confidence: 99%
“…46 Tumor necrosis factor α is also produced through the calcium and zinc binding protein S100A8 as an endogenous ligand for Toll-like receptor-4 in bone marrow-derived macrophages, thereby contributing to NASH-associated inflammation. 47…”
Section: Death Receptorsmentioning
confidence: 99%